2005
DOI: 10.1007/s10765-005-5574-6
|View full text |Cite
|
Sign up to set email alerts
|

Density Equation for Saturated 3He

Abstract: A density equation for saturated vapor and liquid 3 He is presented based on 205 experimental measurements for temperatures greater than 0.2 K collected after a careful survey of the literature. The average deviation of the densities predicted by the equation against the experimental values is 0.39%. There are only 16 points with deviations larger than 1%. This equation is valid for both liquid and vapor densities of 3 He up to the critical temperature of 3.3157 K. The form of the equation satisfies known scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although the rectilinear diameter rule has recently satisfactorily verified for some specific substances, 67 it is generally nowadays considered incorrect for the full group of elements and compounds, and non-analytic contributions determine the behaviour when approaching the critical point. 68 The relative importance of the various non-analytic terms determining the asymptotic behaviour is difficult to assess and remains an actual topic of experimental and theoretical investigations.…”
Section: Among Confirmations Limitations Extensions and Alternativementioning
confidence: 99%
“…Although the rectilinear diameter rule has recently satisfactorily verified for some specific substances, 67 it is generally nowadays considered incorrect for the full group of elements and compounds, and non-analytic contributions determine the behaviour when approaching the critical point. 68 The relative importance of the various non-analytic terms determining the asymptotic behaviour is difficult to assess and remains an actual topic of experimental and theoretical investigations.…”
Section: Among Confirmations Limitations Extensions and Alternativementioning
confidence: 99%
“…However, the big difference between 3 He and 4 He quantum statistics should not be neglected. 4 He obeys Bose-Einstein (BE) statistics and transitions to superfluid below 2.172 K through BE condensation. But 3 He obeys Fermi-Dirac statistics and becomes superfluid only below 2.6 mK through a condensation similar to the BCS mechanism of a superconductor.…”
Section: Reference Data Sources and Analysismentioning
confidence: 99%
“…The temperature dependence of the surface tension should be quite different between 3 He and 4 He, since the ripplons on the latter might be damped, at least at very low temperatures, because of the substance's large bulk viscosity. The internal excitations in 3 He should also be different from 4 He. An experiment by Guo et al [14] on 3 He floating on bulk liquid 4 He has shown a quadratic temperature dependence of the surface tension.…”
Section: Reference Data Sources and Analysismentioning
confidence: 99%
See 2 more Smart Citations